Inflation Expectations, Learning and Supermarket Prices - Cavallo, Alberto (2016)
Information frictions play a central role in the formation of household inflation expectations, but there is no consensus about their origins. We address this question with novel evidence from survey experiments. We document two main findings. First, individuals in lower-inflation contexts have significantly weaker priors about the inflation rate. This finding suggests that rational inattention may be an important source of information frictions. Second, cognitive limitations also appear to be a source of information frictions: even when information about inflation statistics is made readily available, individuals still place a significant weight on less accurate sources of information, such as their memories of the price changes of the supermarket products they purchase. We discuss the implications of these findings for macroeconomic models and policy-making.